2011
DOI: 10.1186/ar3500
|View full text |Cite
|
Sign up to set email alerts
|

Soluble receptor activator of nuclear factor κB ligand/osteoprotegerin ratio is increased in systemic lupus erythematosus patients

Abstract: IntroductionSystemic lupus erythematosus (SLE) patients have lower bone mineral density and increased fracture risk when compared with healthy individuals, due to distinct factors and mechanisms. Bone remodeling is a tightly orchestrated process dependent on several factors, including the balance between receptor activator of nuclear factor κB ligand (RANKL) and osteoprotegerin (OPG).Our aim was to assess serum OPG and soluble RANKL (sRANKL) levels as well as sRANKL/OPG ratio in female SLE patients and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
(24 reference statements)
2
11
1
3
Order By: Relevance
“…Similar to RA, SLE is associated with increased production of pro-inflammatory cytokines that affect the RANKL pathway 6 . Bone micro-architecture and strength may be modified in patients with SLE, even if untreated with glucocorticoids 7 .…”
Section: Bone Changes In Rheumatic Diseases Independent Of Glucocortimentioning
confidence: 99%
“…Similar to RA, SLE is associated with increased production of pro-inflammatory cytokines that affect the RANKL pathway 6 . Bone micro-architecture and strength may be modified in patients with SLE, even if untreated with glucocorticoids 7 .…”
Section: Bone Changes In Rheumatic Diseases Independent Of Glucocortimentioning
confidence: 99%
“…As mentioned, glucocorticoids can favor bone resorption by increasing RANKL/OPG ratio. One study found that SLE patients have lower OPG levels, compared to controls but previous reports of these markers in SLE patients did not evaluate bone mineral density [31,32].…”
Section: Introductionmentioning
confidence: 95%
“…Sistemik enflamasyon, osteoklastik aktiviteyi arttırarak ve osteoblastik aktiviteyi azaltarak kemik kaybına katkıda bulunmaktadır. SLE'li hastalarda kemik yeniden yapılanmasında önemli olan RANKL/OPG oranında artış saptanmış, artmış osteoklastik uyarının kemik kaybında etkili olduğu ifade edilmiştir (58). Aktif hastalıkta, TNF seviyeleri ve oksidize LDL seviyelerinde artış olduğu belirtilmiştir (10).…”
unclassified